Gospel Parallels/Parallel Gospels - Kloppenborg, John S. (Biblical theology bulletin, 2014)
Zeba Crook's Parallel Gospels, mainly for use by undergraduates and students who lack Greek, takes the genre of the Gospel synopsis in innovative and helpful directions. Crook's addition of texts of the “Sayings Gospel Q” and the Gospel of Thomas enhance the utility of his synopsis; Crook's innovative and controversial English translation is designed to maximize the user's ability to see small differences and critical similarities; and his display and alignment of parallels lets the user see what other many synopses obscure.